Converging Luminosity in Column‐Sprite Filaments - Z. Gomez Kuri; S. Soula; T. Neubert; J. Mlynarczyk; C. Köhn (Geophysical Research Letters)
Abstract Sprites are electrical discharges in the mesosphere powered by the quasi‐electrostatic field following a cloud‐to‐ground lightning stroke. They are luminous structures with tendrils formed by a space charge wave with high electric fields that ionizes the atmosphere, excites optical emissions and leaves a trail of enhanced densities of electrons, and negative and positive ions. The duration of the luminous streamers in sprites is usually ∼1–10 ms. In this study, we present observations of sprite streamer filaments where the upper and lower ends continue to glow for more than 80 ms while the two ends slowly converge and fade. Simultaneous magnetic observations suggest that the field in the mesosphere is maintained at a high value by the long‐lasting continuing current of the causative stroke. We propose that the observation is a signature of currents in the filaments fed by electrons detached from negative ions at the lower origin.